High‐Throughput Melanin‐Binding Affinity and In Silico Methods to Aid in the Prediction of Drug Exposure in Ocular Tissue. Issue 12 (2nd November 2015) - Reilly, John; Williams, Sarah L.; Forster, Cornelia J.; Kansara, Viral; End, Peter; Serrano‐Wu, Michael H.
Abstract : Drugs possessing the ability to bind to melanin‐rich tissue, such as the eye, are linked with higher ocular exposure, and therefore have the potential to affect the efficacy and safety profiles of therapeutics. A high‐throughput melanin chromatographic affinity assay has been developed and validated, which has allowed the rapid melanin affinity assessment for a large number of compounds. Melanin affinity of compounds can be quickly assigned as low, medium, or high melanin binders. A high‐throughput chromatographic method has been developed and fully validated to assess melanin affinity of pharmaceuticals and has been useful in predicting ocular tissue distribution in vivo studies. The high‐throughput experimental approach has also allowed for a specific training set of 263 molecules for a quantitative structure–affinity relationships (QSAR) method to be developed, which has also been shown to be a predictor of ocular tissue exposure. Previous studies have reported the development of in silico QSAR models based on training sets of relatively small and mostly similar compounds; this model covers a broader range of melanin‐binding affinities than what has been previously published and identified several physiochemical descriptors to be considered in the design of compounds where melanin‐binding modulation is desired. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:3997–4001, 2015